PERAN ADMINISTRASI DALAM PERLINDUNGAN HUKUM TERHADAP KERUGIAN KONSUMEN PADA TRANSAKSI BRI LINK DI KOTA KUPANG - Asti Look; Agustin L.M Rohi Riwu; Arnold Sjah (Jurnal Administrasi Terapan, 2025)
The development of digital-based financial services through BRI Link agents has increased public access to banking in Indonesia, especially in areas without direct access to conventional bank branches. However, this convenience is accompanied by legal issues related to consumer losses caused by administrative errors, lack of oversight, or agent misconduct. This study aims to examine the role of administration in providing legal protection for consumers in BRI Link transactions in Kupang City.Using a normative and empirical juridical method with a descriptive-qualitative approach, the study analyzes legal norms, regulations, and practices in the field.The findings reveal that weak administrative supervision, lack of standardized procedures, and limited legal awareness among consumers contribute to unresolved disputes and financial losses. Although Law No. 8 of 1999 on Consumer Protection and other financial regulations exist, their implementation in the context of BRI Link services is not yet optimal.This study recommends improving administrative systems, enhancing public legal literacy, and strengthening supervision by BRI and relevant authorities to ensure fair and effective consumer protection. Keywords: legal protection, administration, BRI Link, consumer rights